2020
DOI: 10.1016/j.nmni.2020.100778
|View full text |Cite
|
Sign up to set email alerts
|

Transmission routes for SARS-CoV-2 infection: review of evidence

Abstract: Highlights Airborne transmission of SARS-COV-2 emphasizes the importance of using face masks in public, crowded and closed places as the most important preventive measure. household contact tracing of index COVID-19 cases can be applied as important part of COVID-19 control programs. Vertical transmission of SARS-COV-2 seems possible, but the risk is very low. in theory, SARS-COV-2 may transmit through oral-anal intercourse, it is unlike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 8 publications
1
48
0
Order By: Relevance
“…Both symptomatic and asymptomatic patients have high SARS-CoV-2 viral load in their nasopharynx and trachea ( Baggio et al, 2020 ), which provides the required conditions for exhaled aerosols to carry the virus. There are conflicting evidences for airborne transmission of SARS-CoV-2 ( Falahi and Kenarkoohi, 2020 ). A study has detected SARS-CoV-2 virus RNA on the surface of an air vent, room air and corridor air in a COVID-19 ward (no patient cough was observed during sampling), and it is found that 63.2% of the samples were positive for SARS-CoV-2, and the concentration level reached 2420 RNA copies / m 3 ( Santarpia et al, 2020 ).…”
Section: Influence Of Human-exhaled Aerosol On the Transmission Of Comentioning
confidence: 99%
“…Both symptomatic and asymptomatic patients have high SARS-CoV-2 viral load in their nasopharynx and trachea ( Baggio et al, 2020 ), which provides the required conditions for exhaled aerosols to carry the virus. There are conflicting evidences for airborne transmission of SARS-CoV-2 ( Falahi and Kenarkoohi, 2020 ). A study has detected SARS-CoV-2 virus RNA on the surface of an air vent, room air and corridor air in a COVID-19 ward (no patient cough was observed during sampling), and it is found that 63.2% of the samples were positive for SARS-CoV-2, and the concentration level reached 2420 RNA copies / m 3 ( Santarpia et al, 2020 ).…”
Section: Influence Of Human-exhaled Aerosol On the Transmission Of Comentioning
confidence: 99%
“…Direct transmission from person to person via aerosolized droplets and transmission from direct contact have been shown, and are widely regarded, as the main routes of transmission for SARS-CoV-2 [ 4 , 5 ]. Some concerns have arisen about potential virus transmission via food, food packaging and common food contact surfaces [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 can remain viable for several hours or days on surfaces, which is considered a transmission route, although apparently less significant than others ( Anelich et al, 2020 ; Chan et al, 2020 ; Chia et al, 2020 ; Colaneri et al, 2020 ; Doremalen et al, 2020 ; Falahi & Kenarkoohi, 2020 ; Guo et al, 2021 ; Leung, 2021 ; Marquès & Domingo, 2021 ). Regarding food products, the current consensus is that there is no evidence that SARS-CoV-2 may be transmitted by food, thus not representing a food safety risk ( Anelich et al, 2020 ; EFSA, 2020 ; WHO & FAO, 2020 ).…”
Section: Introductionmentioning
confidence: 91%